Thermo-mechanical characterization of epoxy nanocomposites with different carbon nanotube distributions obtained by solvent aided and direct mixing. - M. Zarrelli; V. Antonucci; M. Giordano; C. Formicola; F. Piscitelli; M. Lavorgna; A. Martone (eXPRESS Polymer Letters)
Two different routes, namely solvent aided dispersion and direct mixing, were employed to disperse Multi-Walled Carbon Nanotubes (MWNTs) into a mono-component epoxy system used as matrix for advanced composites. In the first route, MWCNTs were diluted in three different solvents (acetone, sodium dodecyl sulfate and ethanol) and then mixed with the matrix by tip sonication. In the second case, carbonaceous nanoparticles were added directly into the hosting system and dispersion was carried out by using three different techniques (mechanical stirring, magnetic agitation and tip sonication). The effects of the solvents and agitation energy were investigated by optical microscopy at micron level, in order assess the more efficient dispersion procedure for the considered epoxy system. It was demonstrated that parameters associated with direct mixing rather than solvent solubility govern MWCNT dispersion. Optical analysis of the nanocomposite morphology evidenced a very low density of MWCNTs micron sized aggregates in the case of direct mixed tip sonicated samples if compared to those obtained by solution aided dispersion. In addition, nanocomposites obtained by sonication showed the lowest density of MWCNTs micron sized aggregates, also when compared with mechanically and magnetically stirred system. Dynamic Mechanical Analysis (DMA) and Thermo-Mechanical Analysis (TMA) results confirm the final result that among the considered direct mixing techniques, the direct tip sonication represents the most efficient route for MWCNT dispersion. Moreover, the mixing temperature of the hosting matrix system represents a fundamental feature in enhancing the MWCNT de-bundling and dispersion. Small X-ray Scattering analysis revealed that a nanosized structure of nanotubes is formed in the case of the tip sonicated samples that is heuristically correlated with both the maximum enhancement of mechanical modulus and the maximum reduction of thermal expansion coefficients.